Personalized pharmacotherapy in psychiatry - Filaković, Pavo (Array, 2009)
The hypothesis of each individual being special and different leading to heterogenity of diseases sets the ground for the concept of personalized medicine. The potential application of personalized medicine in psychiatry, supported by pharmacogenetics and pharmacogenomics, are: personalized medication choice, personalized dosage, anticipation of possible side-effects individually and personalized follow-up treatment with rehabilitation. The authors conclude how the development of pharmacogenomics and pharmacogenetics as well as the nanotechnology based on them, presents a step forward in creating a personalized therapeutic approach in psychiatry. However, the burden of applying the most appropriate therapeutic agent and medication tapering remains based on clinician decision